Strengthening the agency of farmers to engage with their NDCs and other strategic climate policy processes - Chevallier, Romy; Chesterman, Sabrina (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
A challenge impeding greater climate advocacy amongst farmers is the lack of policy capacity and engagement knowledge. These opportunities tend to be monopolised by a relatively small group of farmers who are well-informed and have the necessary capacity to act. There are some practical solutions to strengthen the agency and capacity of NFOs for further inclusion in climate action so that they can proactively seek out participation and assert themselves.